Puerarin attenuates myocardial ischemic injury and endoplasmic reticulum stress by upregulating the Mzb1 signal pathway - Xue, Jiaojiao; Ren, Haolin; Zhang, Qi; Gu, Jing; Xu, Qian; Sun, Jiaxi; Zhang, Lu; Zhou, Ming-Sheng (Frontiers in Pharmacology, 2024)
Objective This study investigated the role of Mzb1 in puerarin protection against heart injury and dysfunction in acute myocardial infarction (AMI) mice. Methods C57BL/6 mice were pretreated with and without puerarin at doses of 50 mg/kg and 100 mg/kg for 14 days before establishing the AMI model. An AMI model was induced by ligating the left descending anterior coronary artery, and AC16 cardiomyocytes were treated with H2O2in vitro. Echocardiography was performed to measure cardiac function. DHE staining, nicotinamide adenine dinucleotide phosphate (NADPH) oxidase assay, and DCFH-DA oxidative fluorescence staining were used to determine reactive oxygen species (ROS) production in vivo and in vitro. Bioinformatics analysis was used to predict potential upstream transcription factors of Mzb1. Results Puerarin dose-dependently reduced myocardial infarction area and injury, accompanied by the improvement of cardiac function in AMI mice. AMI mice manifested an increase in myocardial oxidative stress, endoplasmic reticulum (ER) stress, apoptosis, and mitochondrial biogenesis dysfunction, which were inhibited by pretreatment with puerarin. Puerarin also prevented Mzb1 downregulation in the hearts of AMI mice or H2O2-treated AC16 cells. Consistent with the in vivo findings, puerarin inhibited H2O2-induced cardiomyocyte apoptosis, ER stress, and mitochondrial dysfunction, which were attenuated by siRNA Mzb1. Furthermore, the JASPAR website predicted that KLF4 may be a transcription factor for Mzb1. The expression of KLF4 was partially reversed by puerarin in the cardiomyocyte injury model, and KLF4 inhibitor (kenpaullone) inhibited Mzb1 expression and affected its function. Conclusion These results suggest that puerarin can protect against cardiac injury by attenuating oxidative stress and endoplasmic reticulum stress through upregulating the KLF4/Mzb1 pathway and that puerarin may expand our armamentarium for the prevention and treatment of ischemic heart diseases.